Trends in Myanmar Wall Paintings from the Eleventh to the Twentieth Centuries - Green, Alexandra (Journal of Mekong Societies, 2020)
Wall paintings in Myanmar have a long history. Extant remains date as far back as the eleventh century, and murals continue to be produced today. This paper is based on the survey of more than 150 temples in the central zone of Myanmar, exploring the imagery to consider its role in the construction of religious spaces. This paper argues that sacred biography has remained the most significant theme in Myanmar wall and panel painting from the eleventh through the twentieth and twenty-first centuries. Yet, the 900-year long history of this art form discussed here has recorded a process of visual simplification, and by the twentieth century, the extraction of specific stories from an encompassing narrative, iconic, and decorative formation utilized from the eleventh through the nineteenth centuries indicates a profound shift in the role of murals and painted religious imagery from enveloping and complex systems to primarily merit-making and heuristic devices.